Membrane fusion by Drosophila atlastin does not require GTP hydrolysis. - Crosby, D.; Lee, T.H. (Molecular Biology of the Cell, 2022)
Atlastin (ATL) GTPases undergo trans dimerization and a power strokelike crossover conformational rearrangement to drive endoplasmic reticulum membrane fusion. Fusion depends on GTP, but the role of nucleotide hydrolysis has remained controversial. For instance, nonhydrolyzable GTP analogs block fusion altogether, suggesting a requirement for GTP hydrolysis in ATL dimerization and crossover, but this leaves unanswered the question of how the ATL dimer is disassembled after fusion. We recently used the truncated cytoplasmic domain of wild-type Drosophila ATL (DATL) and a novel hydrolysis-deficient D127N variant in single turnover assays to reveal that dimerization and crossover consistently precede GTP hydrolysis, with hydrolysis coinciding more closely with dimer disassembly. Moreover, while nonhydrolyzable analogs can bind the DATL G domain, they fail to fully recapitulate the GTP-bound state. This predicted that nucleotide hydrolysis would be dispensable for fusion. Here we report that the D127N variant of full-length DATL drives both outer and inner leaflet membrane fusion with little to no detectable hydrolysis of GTP. However, the trans dimer fails to disassemble and subsequent rounds of fusion fail to occur. Our findings confirm that ATL mediated fusion is driven in the GTP-bound state, with nucleotide hydrolysis serving to reset the fusion machinery for recycling.